Interaction-induced zero-energy pinning and quantum dot formation in Majorana nanowires - Escribano, Samuel D.; Yeyati, Alfredo Levy; Prada, Elsa (Beilstein Journal of Nanotechnology, 2018)
Majorana modes emerge in non-trivial topological phases at the edges of specific materials such as proximitized semiconducting nanowires under an external magnetic field. Ideally, they are non-local states that are charge-neutral superpositions of electrons and holes. However, in nanowires of realistic length their wave functions overlap and acquire a finite charge that makes them susceptible to interactions, specifically with the image charges that arise in the electrostatic environment. Considering a realistic three-dimensional model of the dielectric surroundings, here we show that, under certain circumstances, these interactions lead to a suppression of the Majorana oscillations predicted by simpler theoretical models, and to the formation of low-energy quantum-dot states that interact with the Majorana modes. Both features are observed in recent experiments on the detection of Majoranas and could thus help to properly characterize them.
Keywords: hybrid superconductor–semiconductor nanowires; interactions; Majorana bound states; quantum dots

(untitled) - Alicea, J. (Rep. Prog. Phys., 2012)

(untitled) - Beenakker, C. W. J. (Annu. Rev. Condens. Matter Phys., 2013)

(untitled) - Aguado, R. (Riv. Nuovo Cimento Soc. Ital. Fis., 2017)

(untitled) - Oreg, Y.; Refael, G.; von Oppen, F. (Phys. Rev. Lett., 2010)

(untitled) - Lutchyn, R. M.; Sau, J. D.; Das Sarma, S. (Phys. Rev. Lett., 2010)

(untitled) - Kitaev, A. (Ann. Phys. (Amsterdam, Neth.), 2003)

(untitled) - Nayak, C.; Simon, S. H.; Stern, A.; Freedman, M.; Das Sarma, S. (Rev. Mod. Phys., 2008)

(untitled) - Aasen, D.; Hell, M.; Mishmash, R. V.; Higginbotham, A.; Danon, J.; Leijnse, M.; Jespersen, T. S.; Folk, J. A.; Marcus, C. M.; Flensberg, K.; Alicea, J. (Phys. Rev. X, 2016)

(untitled) - Lutchyn, R. M.; Bakkers, E. P. A. M.; Kouwenhoven, L. P.; Krogstrup, P.; Marcus, C. M.; Oreg, Y. (Nat. Rev. Mater., 2018)

(untitled) - Albrecht, S. M.; Higginbotham, A. P.; Madsen, M.; Kuemmeth, F.; Jespersen, T. S.; Nygård, J.; Krogstrup, P.; Marcus, C. M. (Nature, 2016)

(untitled) - Gazibegovic, S.; Car, D.; Zhang, H.; Balk, S. C.; Logan, J. A.; de Moor, M. W. A.; Cassidy, M. C.; Schmits, R.; Xu, D.; Wang, G.; Krogstrup, P.; Op het Veld, R. L. M.; et al. (Nature, 2017)

(untitled) - Zhang, H.; Gül, Ö.; Conesa-Boj, S.; Nowak, M. P.; Wimmer, M.; Zuo, K.; Mourik, V.; de Vries, F. K.; van Veen, J.; de Moor, M. W. A.; Bommer, J. D. S.; van Woerkom, D. J.; et al. (Nat. Commun., 2017)

(untitled) - Nichele, F.; Drachmann, A. C. C.; Whiticar, A. M.; O’Farrell, E. C. T.; Suominen, H. J.; Fornieri, A.; Wang, T.; Gardner, G. C.; Thomas, C.; Hatke, A. T.; Krogstrup, P.; Manfra, M. J.; et al. (Phys. Rev. Lett., 2017)

(untitled) - Zhang, H.; Liu, C.-X.; Gazibegovic, S.; Xu, D.; Logan, J. A.; Wang, G.; van Loo, N.; Bommer, J. D.; de Moor, M. W.; Car, D.; het Veld, R. L. M. O.; van Veldhoven, P. J.; et al. (Nature, 2018)

(untitled) - Mourik, V.; Zuo, K.; Frolov, S. M.; Plissard, S. R.; Bakkers, E. P. A. M.; Kouwenhoven, L. P. (Science, 2012)

(untitled) - Das, A.; Ronen, Y.; Most, Y.; Oreg, Y.; Heiblum, M.; Shtrikman, H. (Nat. Phys., 2012)

(untitled) - Deng, M. T.; Yu, C. L.; Huang, G. Y.; Larsson, M.; Caroff, P.; Xu, H. Q. (Nano Lett., 2012)

(untitled) - Churchill, H. O. H.; Fatemi, V.; Grove-Rasmussen, K.; Deng, M. T.; Caroff, P.; Xu, H. Q.; Marcus, C. M. (Phys. Rev. B, 2013)

(untitled) - Deng, M. T.; Vaitiekėnas, S.; Hansen, E. B.; Danon, J.; Leijnse, M.; Flensberg, K.; Nygård, J.; Krogstrup, P.; Marcus, C. M. (Science, 2016)

(untitled) - Zazunov, A.; Egger, R.; Levy Yeyati, A. (Phys. Rev. B, 2016)

(untitled) - Prada, E.; San-Jose, P.; Aguado, R. (Phys. Rev. B, 2012)

(untitled) - Das Sarma, S.; Sau, J. D.; Stanescu, T. D. (Phys. Rev. B, 2012)

(untitled) - Rainis, D.; Trifunovic, L.; Klinovaja, J.; Loss, D. (Phys. Rev. B, 2013)

(untitled) - Vaitiekėnas, S.; Deng, M. T.; Nygård, J.; Krogstrup, P.; Marcus, C. M. (Phys. Rev. Lett., 2018)

(untitled) - Deng, M. T.; Vaitiekėnas, S.; Prada, E.; San-Jose, P.; Nygård, J.; Krogstrup, P.; Marcus, C. (arXiv, 2017)

(untitled) - Kells, G.; Meidan, D.; Brouwer, P. W. (Phys. Rev. B, 2012)

(untitled) - Liu, C.-X.; Sau, J. D.; Stanescu, T. D.; Das Sarma, S. (Phys. Rev. B, 2017)

(untitled) - Moore, C.; Stanescu, T. D.; Tewari, S. (Phys. Rev. B, 2018)

(untitled) - Liu, C.-X.; Sau, J. D.; Das Sarma, S. (Phys. Rev. B, 2017)

(untitled) - Fleckenstein, C.; Domínguez, F.; Ziani, N. T.; Trauzettel, B. (Phys. Rev. B, 2018)

(untitled) - Dmytruk, O.; Klinovaja, J. (Phys. Rev. B, 2018)

(untitled) - Danon, J.; Hansen, E. B.; Flensberg, K. (Phys. Rev. B, 2017)

(untitled) - Domínguez, F.; Cayao, J.; San-Jose, P.; Aguado, R.; Yeyati, A. L.; Prada, E. (npj Quantum Mater., 2017)

(untitled) - Ben-Shach, G.; Haim, A.; Appelbaum, I.; Oreg, Y.; Yacoby, A.; Halperin, B. I. (Phys. Rev. B, 2015)

(untitled) - Prada, E.; Aguado, R.; San-Jose, P. (Phys. Rev. B, 2017)

(untitled) - Clarke, D. J. (Phys. Rev. B, 2017)

Handbook of Inorganic Compounds - Prada, D. L. (CRC Press, 2011)

(untitled) - Hu, E.-T.; Cai, Q.-Y.; Zhang, R.-J.; Wei, Y.-F.; Zhou, W.-C.; Wang, S.-Y.; Zheng, Y.-X.; Wei, W.; Chen, L.-Y. (Opt. Lett., 2016)

(untitled) - Hövel, M.; Gompf, B.; Dressel, M. (Phys. Rev. B, 2010)

(untitled) - Knapp, C.; Karzig, T.; Lutchyn, R.; Nayak, C. (Phys. Rev. B, 2017)

(untitled) - Kitaev, A. Y. (Phys.-Usp., 2001)

(untitled) - Klinovaja, J.; Loss, D. (Phys. Rev. B, 2012)

(untitled) - Schuray, A.; Weithofer, L.; Recher, P. (Phys. Rev. B, 2017)

(untitled) - Ptok, A.; Kobiałka, A.; Domański, T. (Phys. Rev. B, 2017)

(untitled) - Chevallier, D.; Szumniak, P.; Hoffman, S.; Loss, D.; Klinovaja, J. (Phys. Rev. B, 2018)